Peran Sultan Abdul Hamid II dalam Mempertahankan Tanah Palestina dari Yahudi Tahun 1876–1909 - Ana, Ana Tutik Alawiyah; Muhammad Yusrul Hana (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2025)
Abstract: This study examines the role of Sultan Abdul Hamid II in defending Palestine from the efforts of the Jewish Zionist movement in the period 1876–1909. The focus of the study is directed at the political, diplomatic, and ideological strategies implemented by Sultan Abdul Hamid II to reject the offer of the Zionist figure Theodor Herzl who attempted to purchase Palestinian land for Jewish settlement. This study uses a qualitative method with a literature study approach, referring to primary sources such as the memoirs of Sultan Abdul Hamid II and historical documents of the Ottoman Empire, as well as secondary sources in the form of books, scientific articles, and previous theses. Data analysis was carried out through the stages of heuristics, verification, interpretation, and historiography, with a geopolitical theoretical framework that views the relationship between geographical conditions and political policies. The results of the study show that Sultan Abdul Hamid II rejected all forms of sales of Palestinian land to foreign parties, implemented a Pan-Islamic policy to strengthen Muslim solidarity, and tightened administrative supervision and restrictions on Jewish immigration. This decision not only maintained the territorial integrity of the Ottoman Empire, but also strengthened the political awareness of Muslims regarding the importance of Palestine as a holy land. This research contributes to the historical understanding of territorial defense policy in the context of colonialism and religious nationalist movements in the late 19th and early 20th centuries. Abstrak: Penelitian ini membahas peran Sultan Abdul Hamid II dalam mempertahankan Palestina dari upaya gerakan Zionis Yahudi pada periode 1876–1909. Fokus penelitian diarahkan pada strategi politik, diplomatik, dan ideologis yang diterapkan Sultan Abdul Hamid II untuk menolak tawaran tokoh Zionis Theodor Herzl yang berupaya membeli tanah Palestina sebagai wilayah pemukiman Yahudi. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan, mengacu pada sumber-sumber primer seperti memoar Sultan Abdul Hamid II dan dokumen sejarah Kesultanan Utsmaniyah, serta sumber sekunder berupa buku, artikel ilmiah, dan skripsi terdahulu. Analisis data dilakukan melalui tahapan heuristik, verifikasi, interpretasi, dan historiografi, dengan kerangka teori geopolitik yang memandang keterkaitan antara kondisi geografis dan kebijakan politik. Hasil penelitian menunjukkan bahwa Sultan Abdul Hamid II menolak segala bentuk penjualan tanah Palestina kepada pihak asing, menerapkan kebijakan Pan-Islamisme untuk memperkuat solidaritas umat Islam, serta memperketat pengawasan administratif dan pembatasan imigrasi Yahudi. Keputusan ini tidak hanya mempertahankan integritas wilayah Kesultanan Utsmaniyah, tetapi juga memperkuat kesadaran politik umat Islam terhadap pentingnya Palestina sebagai tanah suci. Penelitian ini berkontribusi pada pemahaman historis mengenai kebijakan pertahanan wilayah dalam konteks kolonialisme dan gerakan nasionalisme religius pada akhir abad ke-19 hingga awal abad ke-20.